Corporate Governance Disclosure in the Banking Sector of Bangladesh: Evidence from the Conventional Private Commercial Banks - Neogy, Taposh Kumar (ABC Journal of Advanced Research, 2024)
Corporate governance is necessary for any organization to be accountable and responsible. This study looked into the relationship between CG mechanisms and CG disclosure levels using five listed conventional PCBs as a sample over a five-year period spanning 2016 to 2020. An unweighted disclosure checklist was utilized in this study to measure CG disclosure levels. To determine whether there is any significant relationship between the level of CG disclosure and CG mechanisms, multiple regression analysis has been done. Based on the empirical results, it can be concluded that there is a significant and insignificant association between CG mechanisms and the CG disclosure levels, but there is only a visible and significant difference in these areas between the sample banks. The results of the multiple regression analysis indicate that the log percentage of female directors does not significantly relate to the levels of CG disclosure. On the other hand, the extent of CG disclosure is significantly associated with other variables, including board members, percentage of audit committee members, and percentage of independent directors, log total assets, log total revenues, and log listing age.